2001
DOI: 10.1109/66.939814
|View full text |Cite
|
Sign up to set email alerts
|

An efficient treatment technique for TMAH wastewater by catalytic oxidation

Abstract: Developers used in photolithography contain toxic tetramethylammoniumhydroxide (TMAH) and this creates a problem of how to properly treat developer wastewater. We have developed a TMAH wastewater treatment technique that consists of a combination of two novel decomposition processes: pyrolyzing TMAH to TMA and decomposing TMA to N 2 , H 2 O, and CO 2 by means of a selective oxidation catalyst for nitrogenous compounds. We have tested a system using this technique in long-term treatment of the actual wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 8 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…For example, that is why 1,2-dihydroxybenzene (1,2-dimethoxybenzene in THM) is observed under both THM [14,22] and conventional pyrolysis [24]. In fact, the high temperature used for quaternary ammonium salts decomposition [25,26] favors excessive decomposition and unwanted reactions rather than a selective base-catalyzed hydrolysis and methylation. Similar to TMAH, TMSH (trimethylsulfonium hydroxide) is an organic base, which has been used as a methylating reagent in organic synthesis [27], requires lower THM temperatures [28,29].…”
Section: Introductionmentioning
confidence: 96%
“…For example, that is why 1,2-dihydroxybenzene (1,2-dimethoxybenzene in THM) is observed under both THM [14,22] and conventional pyrolysis [24]. In fact, the high temperature used for quaternary ammonium salts decomposition [25,26] favors excessive decomposition and unwanted reactions rather than a selective base-catalyzed hydrolysis and methylation. Similar to TMAH, TMSH (trimethylsulfonium hydroxide) is an organic base, which has been used as a methylating reagent in organic synthesis [27], requires lower THM temperatures [28,29].…”
Section: Introductionmentioning
confidence: 96%
“…On the contrary, CMSs showed poor adsorption when the temperature was set to low (i.e., 7°C) and when the temperature was increased from 23 to 40°C, b and q 0 were increased, suggesting endothermic process (Kelleher et al 2001). The typical enthalpy change in physisorption is in the range of 5-40 kJ=mol (1:19-9:56 kcal=mol) and typical enthalpy change in ion exchange is below 2 kcal=mol (Helfferich 1995;Inglezakis and Poulopoulos 2006). The adsorption enthalpy range was in the range of a combination of physisorption and ion exchange.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Therefore, TMAHcontaining wastewater has to be properly treated before it can be discharged to the environment. Research conducted to treat the wastewater includes catalytic oxidation (Hirano et al 2001), biodegradation by aerobic process (Tsuzaki and Nakamoto 1990), anaerobic process (Chang et al 2008), aerobic and anoxic/oxic sequencing batch reactors (Lei et al 2010), and reclamation and reuse by a combination of electrodialysis and ion exchange technology (Sugawara et al 2002;Shibata et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hirano et al (2001), and Kim and Choi (2002) reported catalytic oxidation and photocatalytic degradation of TMAH wastewater. Again Shibata et al (2006) studied ion-exchange resins for TMAH recovery from the wastewater.…”
Section: Introductionmentioning
confidence: 98%